Understanding the Existence of Youth in Strengthening Civil Society and Political Parties: Understanding the Existence of Youth in Strengthening Civil Society and Political Parties - Hasrun Afandi UmpuSinga (CV. Multi Kreasi Media, 2022)
The sovereignty of the people is manifested through the ongoing political participation of citizens, or in other words the political participation of the people should not stop after voting (in elections). The people must actively supervise and engage in the political process continuously. A strong and healthy democracy does not only require a strong political society. Of course, it is important to have a strong political party, a strong leader, and a strong government. However, democracy also requires a healthy and strong civil society. Democracy and civil society are like two sides of a coin, both of which have a relationship that influences each other. If in a country there is a strong civil society, then democracy will be good. And vice versa, if the civil society in a country is bad, then democracy will be sluggish. Law No.40 of 2009, youth are Indonesian citizens aged between 16-30 years, inform from BPS in 2021 states that there are 64.92 million youth in Indonesia or around 23.90% of the total population of Indonesia, from the data above the number of Indonesian youth can have the potential to be a social control. Service is carried out by targeting students, especially students of the Faculty of Social and Political Sciences, University of Lampung, activities are carried out using the face-to-face method (Offline) with an Audience of 42 participants delivered in the form of a Power Point Presentation, with material on the definition of civil society, functions, roles and goals of civil society, factors that influence the growth of civil society, manifestations of civil society, the existence of youth in civil society, definition of political parties, how political parties realize their goals, the portion of youth in the 2014-2019 DPR-RI seats, the role of youth in political parties, the figure of Indonesian youth figures.